What kind of kind is “idiot”? - Mendes, João (2015)
[Excerpt] Introduction Are there any idiots? I mean: are there idiots in the world? There must be! Early in the morning my wife said I am an idiot when for the nth time I try to justify my nth oblivion to put down the toilet seat in our bathroom.[...]